The Need of Establishment of Professional Amil Zakat to Enhance the Future Zakat Development - Muhammad Akhyar Adnan (International Journal of Zakat, 2017)
This is basically a conceptual paper. It discusses and proposes the need of establishment of the so-called Professional Amil Zakat. The remarkable development of zakat in Muslim countries so far has to be appreciated highly. However, several things must be done, since the achievement is still far below the potential power available.Among many factors that contribute to the development of zakat is that the existence and the role of Amil Zakat. Needless to say, Zakat development will be hopeless without them. However, there is not much attention has been paid to them.The paper argues that the development of Amil Zakat will in turn enhance the successfulness of zakat practices in the future. A way to do so is by establishing the official professional body of Amil Zakat, locally, nationally, or globally. The establishment of such body is believed that it will enhance the professionalism, which finally supports the practices of Zakat. Keywords: Zakat, Amil, Assocation, Professionalism, Future Development